Advances in orphan drug development for alpha-1 antitrypsin deficiency: a 2025 update from the FDA and EMA - Höger, Philipp; Ries, Markus; Olivares-Rivera, Arturo; Ersöz, Hilal; Buschulte, Katharina; Fähndrich, Sebastian; Kontogianni, Konstantina; Herth, Felix; Trudzinski, Franziska (Therapeutic advances in respiratory disease, 2026)
Background: Research into safe and effective treatments for alpha-1 antitrypsin deficiency (AATD) has been ongoing for more than four decades. There is still a high medical need for better treatment options: Safe, effective, and convenient therapies that target both the lungs and other AATD organ manifestations are eagerly awaited by patients. - Objectives: The purpose of this study is to provide a quantitative clinical-regulatory insight into the current status of the Food and Drug Administration (FDA) and European Medicines Agency (EMA) orphan drug approvals and designations for compounds intended to treat AATD. - Design: A cross-sectional approach was applied, involving a one-time comprehensive search of relevant databases. - Methods: The primary endpoint of this study was to determine the number and nature of FDA and EMA-approved orphan drugs. The secondary endpoint was the registration of compounds with orphan drug designation status. All database searches were performed since the inception of the FDA database in 1983 and the EMA database in 2000, as well as for all compounds listed in the FDA and EMA drug label databases up to 20 January 2025. The search terms ‘antitrypsin’ and ‘proteinase’ were used. - Results: In 1987, the FDA approved the first human alpha1-proteinase inhibitor, representing the only approved active substance (5%) out of 20 with orphan drug designation in the FDA for the treatment of AATD. Conversely, the EMA has granted orphan drug designation to nine active substances, though none of these have yet been approved. However, there are several new active substances that have been granted orphan drug designation: oral neutrophil elastase inhibitor (FDA 2021, EMA 2025), IgG4 Fc-bound recombinant human AAT (FDA 2022), HSV vector therapy (FDA 2023), and A1AT modulator/protein folding stabiliser (FDA 2023, EMA 2024). Furthermore, the development of RNA interference therapeutics has progressed in the United States and Europe. - Conclusion: The development of new therapies may offer expanded treatment options for patients with AATD in the future. In addition to pulmonary manifestations, extrapulmonary manifestations could also be treated in the future.